The Intervention of Prenatal Gentle Yoga in Reducing Leg Swelling in Mother “I” G4P3A0 through the Utilization of a Digital Module - Rahmadina Nurhanijah; Widya Putriastuti; Rei Anggita; Karwati (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
The third trimester of pregnancy is often accompanied by physiological complaints such as leg swelling, which is caused by uterine pressure and hormonal changes. Non-pharmacological interventions like prenatal gentle yoga have the potential to reduce such discomforts. The use of digital modules can also enhance the effectiveness of education and the involvement of pregnant women. This research employed a descriptive case study with a comprehensive midwifery care approach. The subject was Mrs. "I" G4P3A0, who experienced lower extremity edema during her third trimester. The intervention consisted of prenatal gentle yoga conducted over four weeks, three times per week, guided by an educational digital module. After four weeks of prenatal gentle yoga, results showed the swelling had subsided, the mother experienced improved sleep quality, and she gained a better understanding of the importance of maintaining health during pregnancy through non-pharmacological approaches. Prenatal gentle yoga supported by a digital module proved effective as a complementary therapy to reduce edema in third-trimester pregnant women. This intervention not only provided physical benefits but also increased maternal awareness and participation in maintaining holistic health. It can be concluded that digital module-based prenatal gentle yoga is an effective and innovative approach to reducing third-trimester pregnancy edema. It is recommended to be widely implemented in healthcare facilities and educational institutions, and serve as a basis for developing other interactive digital modules.